Ora zero ovvero l’arte del servire di Christoph Marthaler - Balme, Christopher (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay focuses on the drama Christoph Marthalers Stunde Null oder die Kunst des Servierens. It is undoubtedly one of the most important and commercially successful German-language plays of the late 1990s. Numerous performances in other German theaters and abroad, as well as filming and television broadcasts, contributed to its widespread popularity. I will try to outline the particular aesthetic of the staging. After some brief background on the director and his famous “Marthaler-like” style, I will focus on the genesis and structure of this play. Starting with a detailed analysis of a key scene, I will discuss its crucial aesthetic traits, touching on issues concerning body language, musicality of language and the satirical nature of the Swiss director’s works.